2012
DOI: 10.1016/j.ijhydene.2012.04.064
|View full text |Cite
|
Sign up to set email alerts
|

High hydrogen yield and purity from palm empty fruit bunch and pine pyrolysis oils

Abstract: The benefits of CO 2 sorption enhanced steam reforming using calcined dolomite were demonstrated for the production of hydrogen from highly oxygenated pyrolysis oils of the agricultural waste palm empty fruit bunches (PEFB) and pine wood. At 1 atm in a down-flow packed bed reactor at 600 °C, the best molar steam to carbon ratios were between 2 and 3 using a Ni catalyst. After incorporating steam-activated calcined dolomite as the CO 2 sorbent in the reactor bed, the H 2 yield from the moisture free PEFB oil in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…According to the thermodynamic analysis of the SESR of acetic acid, Zin et al [32] showed that operating at a higher steam/C ratio (up to 4) resulted in higher H 2 yield and purity with lower temperature requirements. According to the thermodynamic analysis of the SESR of acetic acid, Zin et al [32] showed that operating at a higher steam/C ratio (up to 4) resulted in higher H 2 yield and purity with lower temperature requirements.…”
Section: Effect Of Temperature On Sesr Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the thermodynamic analysis of the SESR of acetic acid, Zin et al [32] showed that operating at a higher steam/C ratio (up to 4) resulted in higher H 2 yield and purity with lower temperature requirements. According to the thermodynamic analysis of the SESR of acetic acid, Zin et al [32] showed that operating at a higher steam/C ratio (up to 4) resulted in higher H 2 yield and purity with lower temperature requirements.…”
Section: Effect Of Temperature On Sesr Activitymentioning
confidence: 99%
“…obtaining higher H 2 yields with a higher degree of H 2 purity. According to the thermodynamic analysis of the SESR of acetic acid, Zin et al [32] showed that operating at a higher steam/C ratio (up to 4) resulted in higher H 2 yield and purity with lower temperature requirements.…”
Section: Effect Of Temperature On Sesr Activitymentioning
confidence: 99%
“…The SESR process has been shown to improve the hydrogen production compared to conventional SR and satisfactory results have been reported in the literature after the SESR of methane [17][18][19][20][21] [22]. The benefits of the SESR of biomass compounds compared to SR have also been demonstrated with pyrolysis oils obtained from bunches of palm fruit and pine [23] or waste cooking oil [24]. Other experimental results from the SESR of biomass-derived compounds have been reported in the literature using mixtures of different Ni-Co HT catalysts and calcined dolomite as CO 2 acceptor.…”
Section: Introductionmentioning
confidence: 86%
“…For EFB, some examples are fluidized bed, spouted fluidized bed, transported bed, circulating fluid bed, rotating cone, vortex ablative, augur or screw, entrained flow, microwave, fixed bed, hydropyrolysis and vacuum reactor. The most commonly reported reactors for EFB pyrolysis are bubbling fluid beds [38,40,69,94], circulating fluid beds and transported bed [39,69,95,96], ablative pyrolysis [46,51,97], microwave pyrolysis [98], rotating cone reactor [99] and hydropyrolysis [100]. Table 5 lists the many types of pyrolysis reactors available.…”
Section: Types Of Reactorsmentioning
confidence: 99%